Evaluation of PIK3CA mutations in advanced ER+/HER2-breast cancer in Portugal – U-PIK Project - Peixoto, Ana; Cirnes, Luís; Carvalho, Ana Luísa; Andrade, Maria João; Brito, Maria José; Borralho, Paula; Coimbra, Nuno; Borralho, Pedro M.; Carneiro, Ana Sofia; Castro, Lisandra; Correia, Lurdes; Dionísio, Maria Rita; et al. (Frontiers in Molecular Biosciences, 2023)
Background: Around 40% of ER+/HER2- breast carcinomas (BC) present mutations in the PIK3CA gene. Assessment of PIK3CA mutational status is a requirement for identifying patients eligible for treatment with PI3Kα inhibitors, with alpelisib currently as the only approved tyrosine kinase inhibitor in this setting. U-PIK project aimed to conduct a ring trial to validate and implement the PIK3CA mutation testing in several Portuguese centers, decentralizing it and optimizing its quality at national level. Methods: Eight Tester centers selected 2 samples of patients with advanced ER+/HER2- BC and generated 8 replicates of each (n=16). PIK3CA mutational status was assessed in two rounds. Six centers used the cobas® PIK3CA mutation test, and two used PCR and Sanger sequencing. In parallel, two reference centers (IPATIMUP and the Portuguese Institute of Oncology [IPO]-Porto) performed PIK3CA mutation testing by NGS in the two rounds. The quality of molecular reports describing the results was also assessed. Testing results and molecular reports were received and analyzed by U-PIK coordinators: IPATIMUP, IPO-Porto, and IPO-Lisboa. Results: Overall, five centers achieved a concordance rate with NGS results (allele frequency [AF] ≥5%) of 100%, one of 94%, one of 93%, and one of 87.5%, considering the overall performance in the two testing rounds. NGS reassessment of discrepancies in the results of the methods used by the Tester centers and the reference centers identified one probable false positive and two mutations with low AF (1-3%, at the analytical sensitivity threshold), interpreted as subclonal variants with heterogeneous representation in the tissue sections processed by the respective centers. The analysis of molecular reports revealed the need to promote the use of appropriate sequence variant nomenclature with the identification of reference sequences (HGVS-nomenclature) and to state the tumor cell content in each sample. Conclusion: The concordance rates between the method used by each tester center and NGS validate the use of the PIK3CA mutational status test performed at these centers in clinical practice in patients with advanced ER+/HER2- BC.